PERAN PEMERINTAH DAERAH DALAM MEMPROMOSIKAN PARIWISATA TANJUNG BONGO DI DESA SOASIO KECAMATAN GALELA INDUK KABUPATEN HALMAHERA UTARA - SAMBODE, RETNO; TULUSAN, FEMMY; LONDA, VERY (Sam Ratulangi University, 2019)
This study aims to determine the role of local governments in promoting Tanjung Baong tourismobjects in Soasio Village, Galela Subdistrict, North Halmahera Regency, which are reviewed in planningin promoting an object and implementing and evaluating. Promoting tourism objects aimed at attractingtourists who come by sebap that there must be clear information and the government must also have astrategy to influence tourists to be interested and interested in visiting these attractions. The role of bloodgovernment is very important to realize the wishes of the village government and the community tointroduce Tanjung bongo out and to be better known by the outside community. This study usesqualitative research methods adapted to the title and the problem of the research objective is to determinethe role of local governments the success of local governments in increasing tourist visits can run well.Keywords: The Role of Government Object Promotional Regional Promotion